2020
DOI: 10.1108/pijpsm-03-2020-0035
|View full text |Cite
|
Sign up to set email alerts
|

Police officer self-legitimacy: the role of organizational fit

Abstract: PurposePolice officer perceptions of their own legitimacy can be important in shaping aspects of their performance and other organizational outcomes. The current study uses person-environment fit theory to assess the effects of value congruence with top managers, immediate supervisors and coworkers on officers' perceptions of self-legitimacy.Design/methodology/approachThe study used a cross-sectional survey of nearly 250 front-line police officers from seven municipal police departments in Michigan, Indiana an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Research on supervisor fit found role ambiguity was more likely when misfit in role orientation existed between the officer and supervisor (Ingram, 2013); job satisfaction increased when the fit was high (Ingram and Lee, 2015). In another study, higher officer fit was associated with higher self-legitimacy or confidence in authority (White et al, 2020), and organizational fit with managers, public service motivation and self-legitimacy were positively associated with job satisfaction (White et al, 2021).…”
Section: Person−environment Fitmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on supervisor fit found role ambiguity was more likely when misfit in role orientation existed between the officer and supervisor (Ingram, 2013); job satisfaction increased when the fit was high (Ingram and Lee, 2015). In another study, higher officer fit was associated with higher self-legitimacy or confidence in authority (White et al, 2020), and organizational fit with managers, public service motivation and self-legitimacy were positively associated with job satisfaction (White et al, 2021).…”
Section: Person−environment Fitmentioning
confidence: 99%
“…Originating from organizational psychology, the premise is that the congruence between an individual and their organizational environment may influence outcomes like stress, job satisfaction and turnover (Edwards and Shipp, 2007;Edwards et al, 1998;Kristof-Brown et al, 2005). Recent work suggests that the PÀE fit framework can help build on our understanding of officers in the policing organization (Ingram, 2013;Ingram and Lee, 2015;White et al, 2020White et al, , 2021. Adding to this limited research, we use the personÀenvironment fit framework to explore officers' perceptions of stress, job satisfaction and turnover contemplation.…”
Section: Introductionmentioning
confidence: 99%
“…Public opinion is crucial for police entrenchment or reform, and public sentiment acts as a mechanism for police accountability in at least three ways. First, the sense of “self-legitimacy,” officers’ sense of their right to exercise police power, is at least partially influenced by the degree to which they believe the public supports their efforts (Nix & Wolfe; 2017; D. White et al, 2020).…”
Section: Prior Research On Disparities In Traffic Stopsmentioning
confidence: 99%
“…A few exceptions employed two separate self-legitimacy scales (Gau and Paoline, 2021) or a single external legitimacy scale only (Jonathan-Zamir and Harpaz, 2014). Overall, officer self-legitimacy has only been examined by a relatively small number of procedural justice studies, treated as a PIJPSM 44,5 dependent variable (Gau and Paoline, 2021;Nix and Wolfe, 2017;White et al, 2020), an independent variable (Jonathan-Zamir and Harpaz, 2018) or both (Bradford and Quinton, 2014;Tankebe, 2019;Tankebe and Mesko, 2015).…”
Section: Linkage Between Internal and External Procedural Justicementioning
confidence: 99%
“…One study showed that stronger organizational justice (measured by a composite reflecting both agency and management justice) is inclined to stimulate higher self-legitimacy among officers in a sheriff's department (Nix and Wolfe, 2017). A second study revealed that officers with higher value alignment levels with their supervisors expressed more confidence in their authority (White et al, 2020). Nonetheless, contradictory evidence indicating a statistically nonsignificant relationship between supervisory procedural justice and self-legitimacy is also demonstrated among the US (Gau and Paoline, 2021) and the UK police officers (Tankebe, 2019).…”
Section: Linkage Between Internal and External Procedural Justicementioning
confidence: 99%